2(8n-1)+9=8(2n+8)

Simple and best practice solution for 2(8n-1)+9=8(2n+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(8n-1)+9=8(2n+8) equation:



2(8n-1)+9=8(2n+8)
We move all terms to the left:
2(8n-1)+9-(8(2n+8))=0
We multiply parentheses
16n-(8(2n+8))-2+9=0
We calculate terms in parentheses: -(8(2n+8)), so:
8(2n+8)
We multiply parentheses
16n+64
Back to the equation:
-(16n+64)
We add all the numbers together, and all the variables
16n-(16n+64)+7=0
We get rid of parentheses
16n-16n-64+7=0
We add all the numbers together, and all the variables
-57!=0
There is no solution for this equation

See similar equations:

| 8x-12+1=5x-5 | | 8x+11=5x=32 | | 10-(1)/(15)x=(1)/(10)x | | 4x-28=x+11 | | 1/2(6-2z)=-9/4z-1/8(-4z+6) | | 4u−12u−-17u+-u+-13u=10 | | -20+11x=11x-20 | | b=95+(25+6) | | 2q+15=3q | | 2b-6=12+4b | | 4x^2-12x-352=0 | | 18n-12n=12 | | 3/z+8/2z=2 | | -6/7=-5x | | P=×+3y | | 15x-9x=6 | | 8n^2+32n-30=0 | | 2(3x+60)+2(5x)=360 | | P=3×+2y | | 4x−1=4(x+3) | | -26=4=5x | | 1/5w-5/2=-7/3 | | 7x-191=-2x+142 | | 5x+x•x+6=180 | | 3.5s-10=5.25s | | -72=3(4n-4) | | 0.75(k+20)=2+0.5(k-2) | | 4p-12=2(-p-8) | | 5.25s=3.5s+10 | | 4=0.80b | | 2x-3/10+1/20=x-1/4 | | x2+x3=80 |

Equations solver categories